Efficacy and Safety of a Preemptive Antiviral Therapy Strategy Based on Combined Virological and Immunological Monitoring for Active Cytomegalovirus Infection in Allogeneic Stem Cell Transplant Recipients. (18th May 2016) - Navarro, David; Amat, Paula; de la Cámara, Rafael; López, Javier; Vázquez, Lourdes; Serrano, David; Nieto, José; Rovira, Monserrat; Piñana, José Luis; Giménez, Estela; Solano, Carlos
Abstract : Preemptive antiviral therapy for active CMV infection in allogeneic stem cell transplant recipients guided by immunological and virological parameters minimizes the risk of recurrent viremia in a subset of patients. Abstract: Background. Preemptive antiviral therapy for active cytomegalovirus (CMV) infection in allogeneic stem cell transplant recipients (Allo-SCT) results in overtreatment and a high rate of recurrences. Monitoring of CMV-specific T-cell immunity may help to individualize treatments and minimize these problems. Methods. We conducted a prospective, multicenter, matched comparison-group study to evaluate the efficacy and safety of a novel strategy that consisted of interrupting anti-CMV therapy upon CMV DNAemia clearance and concurrent detection of phosphoprotein 65/immediate-early-1-specific interferon-γ-producing CD8 + T cells at levels of >1 cell/µL (within 30 days after the initiation of therapy). Immunological monitoring was performed on days +7, +14, +21, and +28 after treatment initiation. The primary endpoint was the cumulative incidence of recurrent DNAemia within 2 months after treatment cessation. Secondary endpoints were the length of antiviral treatment courses and the incidence of hematological toxicity. Results. Sixty-one patients were enrolled in the study group. Fifty-six patients were included in the matched-control group. Eleven patients (18%) fulfilled the criteria for antiviral treatment interruption. The cumulative incidence of recurrent CMV DNAemia was significantly lower ( P = .02) in these patients than in patients in the comparative groups. Likewise, the length of antiviral treatment courses was significantly shorter in these patients than that in patients in the matched-control group ( P = .003). No significant differences in the incidence of hematological toxicity was observed between the comparative groups. Conclusions. Our data support the clinical utility of combining immunological and virological monitoring for the management of CMV infection in a subset of Allo-SCT recipients.